Perceptions of English Education Students Regarding the Use of Artificial Intelligence (AI) in English Lessons - Umi Imtitsal Rasyidah; Muh Futuhu Rifqil Aziz; Farida Nova Kurniawati (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2026)
The rapid advancement of technology in education has transformed learning processes in the digital era, particularly through the emergence of Artificial Intelligence (AI). In English language learning, AI platforms such as ChatGPT are increasingly used to support academic activities, improve writing skills, provide real-time feedback, and enable personalized learning. This study aims to explore students’ perceptions of AI use in English language learning. This research employed a qualitative descriptive approach. Data were collected through participatory observation, semi-structured interviews with 18 questions, and documentation. The participants were 30 students of the English Education Study Program at the Faculty of Education and Teacher Training, UIT Lirboyo Kediri. Data were analyzed using the Miles and Huberman interactive model, including data collection, reduction, display, and conclusion drawing. The findings indicate that students perceive AI as an effective and efficient tool for enhancing English learning, particularly in writing. AI provides immediate feedback on grammar, vocabulary, spelling, and organization, supporting independent learning. However, concerns about overreliance on AI were identified, as it may hinder critical thinking. Therefore, AI should be used as a supportive tool, complemented by proper digital literacy to ensure ethical and effective use.